PEMBERDAYAAN MASYARAKAT MELALUI OPTIMALISASI PENGELOLAAN WAKAF TUNAI (Studi Kasus pada LAZ Baitul Maal Hidayatullah dan Yatim Mandiri Cabang Lampung) - Ghafur, Ruslan Abdul; Nur, Isnayati (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2013)
This research includes into field research using descriptive comparative-analyticmethod compare two cash donation management institutions Baitul Maal Hidayatullah and Yatim Mandiri branch of Lampung from managerial aspectsand its management. From the research it was found that the managerial aspects,both institutions have been carrying out management functions well, although there are still many obstacles encountered. Constraints that exist are more focused on positioning discrepancy employees that do not comply with the expertise that is not equally effective. In funding aspect and utilization of cash donation is still traditionally and consumer organized, because the funding model was only intended to supplement the inventory donation asset that have been there without doing more innovations especially in the field of public economics